Effectiveness of Internal Audit Reporting in the Northern Provincial Council of Sri Lanka - Anojan, V. (3rd International Symposium on Social Sciences and Humanities (IRSSSH) 2020, NCAS, Sri Lanka, 2020)
The main purpose of the study is to find out significant factors affecting the effectiveness of internal audit reporting in the Northern Provincial Council of Sri Lanka. Factors cover accountability & transparency, audit evidence, competence of internal auditors, independence of internal auditor, materiality, performance audit, true and fair view, and usage of resources and facilities. Primary data was used in this study, were collected from heads of the departments or divisions and internal auditors of the Northern Provincial Council through a Likert scale questionnaire. Descriptive and inferential statistics were performed with the help of SPSS. Mean analysis confirmed that internal audit evidence and internal audit reporting is above satisfaction level in the Northern Provincial Council of the Sri Lanka. Regression analysis confirmed that factors tested in this study significantly impact the effectiveness of internal audit reporting in the Northern Provincial Council of Sri Lanka, those factors have 67.5% impact. Further, correlation analysis revealed that accountability and transparency, independence of internal auditors, true and fair view, and performance audit have significant positive relationships with the effectiveness of internal audit reporting in the Northern Provincial Council of Sri Lanka. According to the findings of the study, top management and internal auditors should consider accountability and transparency, independence of internal auditor, performance audit, true and fair view, and usage of resources and facilities, to increase the effectiveness of internal audit reporting in the Northern Provincial Council and other similar government sector institutes in Sri Lanka.
Keywords: Internal Audit; Reporting